Giá trị cảm nhận và ý định sử dụng thương mại di dộng: Vai trò của giá trị tri thức và giá trị dựa trên điều kiện - Nguyễn Hữu, Khôi (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2019)
This study is conducted to contribute to a more comprehensive understanding regarding the relationship among perceived value components and between perceived values with behavioral intention in mobile commerce context. Accordingly, epistemic value and conditional value are hypothesized to have impacts on utilitarian, hedonic and social value. Besides, these perceived values are hypothesized to have positive influence on intention to use mobile commerce. The testing results on a sample of 350 mobile services consumers by using SmartPLS software indicate that the hypotheses are supported by data except for the impact of social value on behavioral intention and the influence of conditional value on hedonic value are insignificant. Based on these remarkable results, this study has contributions in both academic and practical perspectives,
Keywords: Perceived Value; Epistemic Value; Conditional Value; Intention To Use; Mobile Commerce